ขบวนการประชาสังคมในประเทศไทย : ศึกษากรณีการก่อตัวของสงขลาประชาคม - ทศพล แก้วประพันธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This thesis aims at finding why and under what circumstances the Songkhla Prachacom Movement is formed. The formation of the movement is discovered to be triggered by not only the deterioration of natural resources and environment in Songkhla Province as a consequence of the industrialization policy and the economic and social development plans but also the centralization of state policy-making and implementation. However the emergence of the Songkhla Prachacom Movement results directly from an attempt of some civil groups to solve the existing problems themselves. The movement also applies the concept of civil society to its operation in order to strengthen itself.